2011
DOI: 10.1089/jpm.2011.0179
|View full text |Cite
|
Sign up to set email alerts
|

Giving Voice to Patients' and Family Caregivers' Needs in Chronic Heart Failure: Implications for Palliative Care Programs

Abstract: Background: The American College of Cardiology Foundation/American Heart Association (ACC/AHA) Guidelines for the Management of Heart Failure recommend palliative care in the context of Stage D HF or at the end of life. Previous studies related to heart failure (HF) palliative care provide useful information about patients' experiences, but they do not provide concrete guidance for what palliative care needs are most important and how a palliative care program should be structured. Objectives: Describe HF pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 38 publications
3
80
0
3
Order By: Relevance
“…Other studies have reported similar findings pertaining to the earlier timing of PC. [50][51][52] This point was further emphasized in our formative evaluation by the fact that two patients experienced sudden, unexpected cardiac death within two weeks of enrollment, before the CYC sessions were started, and another died six weeks after enrollment just after completing sessions. Though the sample size was small, we experienced an almost 30% sudden death rate.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported similar findings pertaining to the earlier timing of PC. [50][51][52] This point was further emphasized in our formative evaluation by the fact that two patients experienced sudden, unexpected cardiac death within two weeks of enrollment, before the CYC sessions were started, and another died six weeks after enrollment just after completing sessions. Though the sample size was small, we experienced an almost 30% sudden death rate.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because of this unpredictability, patients and their families face numerous uncertainties in the future, such as whether they can work, take trips, or attend family events. [5][6][7] Such unpredictability also poses challenges for advance care planning. For example, in our earlier study to identify palliative care needs and support preferences in heart failure (HF) care, some participants and their informal (family) caregivers avoided discussing the future because the future was so uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our earlier study to identify palliative care needs and support preferences in heart failure (HF) care, some participants and their informal (family) caregivers avoided discussing the future because the future was so uncertain. 6 Thus, the nature of HF makes it particularly important to understand how patients and their caregivers perceive their changing health and healthcare needs, and how these perceptions relate to concerns and questions about what lies ahead.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers expressed need to understand the illness milestones and the disease progression. They wanted to be made aware of what would be a concerning point along the illness course or what resources would be needed by the patient [8].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of symptoms patients will experience on a daily basis was the third point. Incorporating advanced care planning would assist on providing a prospective about the uncertainties of heart failure [8].…”
Section: Discussionmentioning
confidence: 99%